A narrative position analysis of asylum seekers’ stories about waiting for their permit permission in Norway - Solbue, Vibeke (Frontiers in Education, 2024)
This research aims to understand more about the consequences that living for many years without a residence permit in Norway can have for asylum seekers. As a narrative inquiry study (Clandinin, 2022), the research puzzle is asylum seekers in Norway without a resident permit. This article focuses on one family. The data material is collected with different methods, such as field talks, interviews, pictures, and messages on Messenger. The study uses narrative position analysis (Bamberg, 1997), and it analyses the narrated story on three different levels. The main results show that the parents of the family tend to position themselves differently according to whether they are talking about the time before they fled, the time while fleeing or after the fled. When talking about the decision to flee, they present themselves as active subjects with high agency. They have the ability to take active decisions and play an essential role for the family's life. The analyses reveal three different master narratives; being a parent, being a citizen of a community and being an asylum seeker. I conclude with thoughts about the waiting period as an asylum seeker, and I ask whether Norway respects and ensures human rights. Is the situation of long-term asylum seekers and the condition of the waiting period in different reception centres a form of national abuse of power?